PENGARUH NEGATIF MEDIA SOSIAL TERHADAP MOTIVASI BELAJAR MAHASISWA GENERASI Z DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Olivia Yohani Wati; Siti Sarah; Maria Angelica D; Nataliya Pratiwi; Tan Evan Tandiyono (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The dynamics of student behavior in the digital era are closely linked to the intense utilization of social media platforms, which triggers complex psychological and cognitive shifts. This study examines the negative impacts of social media on the learning motivation of Generation Z students at Universitas 17 Agustus 1945 Surabaya. Using a qualitative approach with a descriptive phenomenological design, this research explores the live experiences of digital native students. Data collection was conducted through in-depth interviews, continuous behavioral tracking, and documentation. The results indicate that high intensity and uncontrolled social media usage, particularly on endless-scrolling platforms like TikTok, generate significant cognitive distraction. This condition manifests in cognitive overload and task-switching inefficiency, which directly stimulate academic procrastination. Furthermore, the constant exposure to digital validation features (likes, comments) erodes students' intrinsic learning motivation by replacing intellectual satisfaction with instant gratification. On the other hand, extrinsic motivation experiences severe distortion due to upward social comparison and the Fear of Missing Out (FOMO), leading students to question the relevance of long-term formal education. Despite these vulnerabilities, the study also reveals that students possess internal resilience factors derived from deeply held personal values and inspirational figures, which serve as psychological protective barriers. This research underscores the urgent need for integrating digital literacy and time-management interventions within the higher education ecosystem to restore academic engagement.